Dogfennel (Eupatorium capillifolium): Biology and Control - Brent A. Sellers; Jason A. Ferrell (EDIS)
Dogfennel is currently the number one most commonly occurring pasture weed in Florida. Many people think it is only unsightly, but it causes significant bahiagrass yield loss and can cause dehydration when ingested by cattle. This revised 3-page fact sheet was written by B. A. Sellers and J. A. Ferrell and published by the UF Department of Agronomy, September 2011.